Desarrollo de heurísticas de usabilidad para aplicaciones de realidad virtual utilizando la metodología prometheus. - Robalino., Jefferson (2018)
The arrival of Virtual Reality "VR" to smartphones through its large screens and gyroscopes, accessories included inside of the devices, has potentiated the number of VR application development and this has become evident in application stores that statistically have had a significant increase in the number of downloads of this type of applications, despite this increase there are several things that must be improved, one of its main problems is the usability considering that it is important that users can use this type of applications intuitively. Many efforts have been made to create usability heuristics for virtual reality, but a suitable heuristic creation methodology has not been used for a kind of application, specifically for Virtual Reality. Next, we present a package of usability heuristics for VR, resulting from the applied methodology, these will help in the creation and measurement of new applications, as well as for the development and control of usability in VR applications, and these have been tested in prototypes and with trained evaluators in the subject of heuristic evaluation.